Measurement and evaluation of China’s mainland AS-level topology - ZHANG Guo-qiang1; ZHANG Guo-qing1; FAN Jing1 (Tongxin xuebao)
Through large-scale active probing from multiple vantage points,more comprehensive and accurate AS graph for China’s mainland was obtained,after which a detailed characterization was made for it.By comparison with various popular network models at present,It was found that PFP model accurately reproduces china AS graph,which indicates that China’s mainland’s AS graph shows similarities to the global one.Based on this,a hypothesis was proposed that the Internet AS level topology may have inherent topological similarity under proper partitioning operations.